AI-GENERATED PHOTOBOOKS FOR EDUCATIONAL USE - Khalique, Fehmina; Sharma, Deepika; Singh, Jagtej; Singh, Preetjo; Bajpai, Priya; Pahariya, Sakshi; Barde, Saudagar Subhash (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The fast development of artificial intelligence has created new opportunities in the creation of educational materials, previously, the so-called AI-based photobooks to learn visually. This paper will look into the creation, application, and instructional worth of AI-created photobooks on various education levels. Based on the existing models of visual cognition and multimedia education, the study seeks to understand how visual images and layouts created by AI could contribute to student engagement, understanding, and memorization. It employed a mixed-methods research design, which became a combination of surveys, controlled experiments, and qualitative analysis of photobook samples to determine the reactions and usability of learners. Students and teachers of primary, secondary, and higher educational establishments were randomly chosen to participate in this study with the help of purposeful and stratified sampling. The paper defines the technological process of creating AI-generated photobooks, including prompt engineering, image-generating applications, content selection guidelines, and layout designing plans in accordance with the educational requirements. It also breaks down the ways such photobooks could be used in various subject areas like science, history, and language learning and demonstrates that differentiated instruction can be achieved with the application of customizable visual materials. The benefits of AI-generated content in terms of accessibility are specifically highlighted, specifically by the students with visual, cognitive, or linguistic impairments.